COMPARATIVE ANALYSIS OF RUSSIAN AND BRITISH APPROACHES TO NEUROPSYCHOLOGICAL DIAGNOSTICS AND NEUROPSYCHOLOGICAL REHABILITATION - Yu. V. Mukhitova; M. D. Selkin; I. L. Gureeva; N. A. Gomzyakova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. This article is devoted to the comparative analysis of the Russian and British approaches to restoration of the highest mental functions in patients with neurological disorders.The applicability of development of effective programs for neuropsychological rehabilitation of neurological patients is represented, where one of the main directions is the reconstruction of higher mental functions.Results. This article shows the importance of cooperation and understanding of specialists among the multidisciplinary team in medical rehabilitation system. The history of origin of the concept «multidisciplinary approach» is cited, it was spoken about by V. M. Bekhterev for the first time, emphasizing the necessity of multidisciplinary study of neuropsychic system of a healthy and ill person. Special aspects of rehabilitation process in Russia and in England were considered. Results of the comparison of neuropsychological rehabilitation models of two countries were presented. Conclusions. Further guidelines of cooperation between Russian and foreign neuropsychologists were identified. The attention is focused on determination of rehabilitation potential and inclusion of the patient and his family in rehabilitation process as it allows to solve problems of insufficiency of motivation, a self-assessment and to prevent emotional violations, increasing quality of life of patients.